Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1984
DOI: 10.1017/s0305000900005584
|View full text |Cite
|
Sign up to set email alerts
|

The current status of the motherese hypothesis

Abstract: Partially conflicting results from correlational studies of maternal speech style and its effects on child language learning motivate a comparative discussion of Newport, Gleitman & Gleitman (1977) and Furrow, Nelson & Benedict (1979), and a reanalysis of the original Newport et al. data. In the current analysis the data are from two groups of children equated for age, in response to the methodological questions raised by Furrow et al.; but, in line with the original Newport et al. analysis, linguistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
211
2
14

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(244 citation statements)
references
References 20 publications
(26 reference statements)
11
211
2
14
Order By: Relevance
“…Hence, in order to make more profound conclusions concerning these matters, further investigations are in order and even up until the third year of children's life. In addition, because according to some earlier findings the way an individual mother talks to her child is significantly determined by the child's own linguistic and communicative ability (see Gleitman, Newport & Gleitman, 1984;Hampson & Nelson, 1993;Lloyd & Masur, 2014;Masur, 1982;Snow, 1995), it would be interesting to study to what extent maternal contingency is stable over the course of time during significant changes in children's linguistic skills. However, in a study by Flynn and Masur (2007), maternal responsiveness and intrusive attentional directiveness demonstrated considerable stability between the children's ages of 0;10 and 1;9.…”
Section: Bidirectional Nature Of the Relationship Between Maternal Vementioning
confidence: 99%
“…Hence, in order to make more profound conclusions concerning these matters, further investigations are in order and even up until the third year of children's life. In addition, because according to some earlier findings the way an individual mother talks to her child is significantly determined by the child's own linguistic and communicative ability (see Gleitman, Newport & Gleitman, 1984;Hampson & Nelson, 1993;Lloyd & Masur, 2014;Masur, 1982;Snow, 1995), it would be interesting to study to what extent maternal contingency is stable over the course of time during significant changes in children's linguistic skills. However, in a study by Flynn and Masur (2007), maternal responsiveness and intrusive attentional directiveness demonstrated considerable stability between the children's ages of 0;10 and 1;9.…”
Section: Bidirectional Nature Of the Relationship Between Maternal Vementioning
confidence: 99%
“…Thus, it is unlikely that the developmental effect is due to imitation or priming. A more likely explanation is that adults used more TL structures early in children's acquisition as a general adjustment to make their utterances comprehensible to children (motherese; Bohannon & Marquis, 1977;Gleitman, Newport & Gleitman, 1984). Importantly, the early TL bias shown in Figure 3 suggests that parents' full locatives information for children to learn LT-biased verbs.…”
Section: The Developmental Trajectory Of Structural Choice In the Engmentioning
confidence: 99%
“…An alternative interpretation of the same phenomenon places far more emphasis on the child's naturally developing abilities. The changes in adult speech represent accommodation to the child's developing competence (Gleitman et al, 1984). From this perspective adults change what they talk about, and how they talk, to fit in with the child's abilities to understand, but such adjustments follow rather than lead the child on to the next stage.…”
Section: Discussionmentioning
confidence: 99%
“…However, Gleitman, Newport and Gleitman (1984) argue that the simplest CDS might not be the best basis for learning language. They studied children at the telegraphic speech stage and found that mothers who produced more complex CDS had children who were linguistically more advanced.…”
Section: Language Input Studies Of Ordinary Childrenmentioning
confidence: 99%